Karakteristik Edible Film Selulosa Batang Jagung (Zea mays) dengan Penambahan Sorbitol - Afriyanti, Afriyanti; Asmoro, Novian Wely; Widyastuti, Retno; Arifin, Muhammad (Program Studi Teknologi Pangan, 2020)
Cellulose is the main constituent of cell walls in plants, cellulose (C6H10O5) n is a long-chain polymer of polysaccharides, 1,4-beta-D-glucose. Cellulose can be extracted from corn stalks with a yield of 35.61%. This cellulose can be used as a base for making edible films other than starch. Improving the physicochemical quality of edible film can be done by adding a plasticizer, such as sorbitol. The aim of this research is to produce edible film from cellulose corn stalks with the addition of sorbitol as a plasticizer. The experimental design used in this study was a completely randomized design with one factor, namely the concentration of Sorbitol (A) with 6 treatment levels, namely A1 = 0% (control), A2 = 1 ml; A3 = 2 ml; A4 = 3 ml; A5 = 4 ml and A6 = 5 mL. Each treatment was repeated three times in order to obtain experimental units 6 x 3 = 18 experimental units. The product analysis carried out was the thickness, tensile strength, and pH of the edible film. The results showed that the best edible with the highest tensile strength value was obtained when the addition of 4 ml sorbitol was 9.45 MPa.